Modern Japan : a history in documents - Huffman, James L., 1941- (New York : Oxford University Press, 2004)
James L. Huffman combines primary sources, including newspapers, diaries, cartoons, literature, wood block prints, maps, memoirs, photographs, and political essays, to present a narrative of Japan's history from 1600 through the twentieth century, focusing on cultural and economic, as well as political and intellectual, developments.
Includes index.
Keywords: Japan -- History -- 1868-; Japan -- History -- Tokugawa period, 1600-1868.; Japan -- History -- 1868- -- Sources; Japan -- History -- Tokugawa period, 1600-1868 -- Sources